Teaching Reading through Survey, Question, Read and Write (SQRW) at Junior High School 20 Padang - Alicia, Dona (Institut Agama Islam Negeri Imam Bonjol Padang, 2017)
This research was Classroom Action Research to analyze students’ reading comprehension through SQRW. In this research, researcher used random sampling in selecting the participant and answering the question of questionnaire. In collecting the data, the researcher did observation and used reading task, test, teacher’s diary and Questionnaire. The subject of the study is the second year students of SMP Negeri 20 Padang, The subject consists of 40 students, 23 male and 18 females. From the data that have been found, they have good ability in serving, answering questions, reading and writing. It means the ideal passing score is at least 75%. This study was stopped when 90% of the students, subject of this study have reached the passing grade. It is recommended that English teacher of junior high school use the SQRW in the classroom, the teacher must to be able to support the students to learn reading by using SQRW and also the teacher must consider the best teaching in developing the use SQRW.